Effect of operating parameters on performance and emissions of a diesel engine fueled with ternary blends of palm oil biodiesel/diethyl ether/diesel by Taguchi method. (1st September 2020) - Uslu, Samet; Aydın, Mustafa
Highlights: Taguchi design was applied to find the optimum engine running parameters for best engine responses. DEE ratio, palm oil ratio, advance and load have been chosen as affecting factors to engine outcomes. Proposed Taguchi model is capable for mapping engine outcome paradigms by high accuracy. Abstract: Since operating factors play an important role on engine emissions and performance, it is important to explore the common influence of several operating factors on diesel engine performance and emission parameters. In this paper, it was aimed to investigate the effects of diethyl ether (DEE) ratio, palm oil ratio, injection advance and engine load on diesel engine performance and emission parameters. Test were planned based on Taguchi L27 orthogonal array (OA) that considered DEE ratio, palm oil ratio, injection advance and engine load as factors and brake thermal efficiency (BTE), brake specific fuel consumption (BSFC), exhaust gas temperature (EGT), carbon monoxide (CO), hydrocarbon (HC), nitrogen oxides (NOx ) and smoke emissions as responses. The effects of engine operating parameters on responses were determined by variance analysis (ANOVA). Considering the outcomes of the study, optimal levels of each factor were assigned from the point of engine performance and emission attributes. The highest signal-to-noise (S/N) ratios of BTE, BSFC and EGT were observed with the low DEE ratios, low injection advance values and average engine load. Overall, the highest S/N ratios achieved for emission responses were obtained with high DEE percentages and 35 CAs. While the highest S/N ratios for CO and smoke were seen with 20% palm oil, the highest S/N ratios were obtained with 0% palm oil for all other responses. These results showed that ANOVA-supported Taguchi design method is an effective tool with the aim of define the effect rates of engine operating parameters.